Ethnopharmacological Use and Biological Activities of Tragia involucrata L. - Pallie, M.S.; Perera, P.K.; Kumarasinghe, N.; Arawwawala, M.; Goonasekara, C.L. (Evidence-Based Complementary and Alternative Medicine, 2020)
Plants have been utilized as medicines to treat various ailments since ancient times. Formulations made by plant materials have been used in traditional, complementary, and alternative medicine and remain widespread in both developing and developed countries. In developing countries, traditional medicines are widely practiced due to its accessibility and a1ordability, while in developed countries, complementary and alternative medicine are widely popular due to the adverse e1ects of chemical drugs. Tragia involucrata Linn. (family: Euphorbiaceae) is a highly used medicinal plant used in both Sri Lankan and Indian traditional medical systems. Since this plant is a weed, it is being extensively destroyed due to the lack of knowledge regarding the medicinal value of this plant. Hence, the objective of this study was to collect data on the medicinal value of this plant by correlating its scienti8cally validated biological activities with its ethnopharmacological uses. An attempt was made to gather as much information available regarding the ethnopharmacological uses and scienti8cally validated biological activities of Tragia involucrata through authentic traditional texts, scienti8c journals, and other authentic texts regarding medicinal plants. ,us, the review provides an insight to the capability of Tragia involucrata to be used as a monoherbal formulation for diseases pertaining to multiple systems of the body. With all the scienti8cally validated biological activities and the ethnopharmacological uses, Tragia involucrata may qualify as a potent candidate to be developed into a phytomedicine to be utilized as both a preventive and as a therapeutic agent.
Keywords: Tragia involucrata Linn.; ethnopharmacological uses